INFORMATION BASES OF THE COURSE «ORGANIZATIONAL PLANNING» FOR STUDENTS OF THE SPECIALITY 032001 «DOCUMENTATION MANAGEMENT AND ADMINISTRATIVE DOCUMENTATION SUPPORT » - Vyacheslav V. Persianov; Aleksandr V. Gordeev (Статистика и экономика, 2016)
The information basics of the course «Organizational planning» are describes inthe article on the basis of three clusters of information training: basic, professional andtechnological. The experimental study has shown high efﬁciency in Tula State Lev Tolstoy Pedagogical University of the proposedmethodological technique.